A report of a South African university's management of undergraduate nursing students' teaching and learning following the COVID-19 interruptions - Olivia B. Baloyi; Mary Ann Jarvis; Ntombifikile G. Mtshali (AOSIS, 2022)
The coronavirus disease 2019 (COVID-19) pandemic exposed an absence of blueprints to avert an education disaster. In South Africa, in line with Alert Level-5, adhering to lockdown restrictions, higher education institutions (HEIs) closed, necessitating the transition to online teaching and learning. The HEIs, inclusive of the nursing discipline, needed to develop comprehensive plans and a rigorous follow-up scheme in order to ensure that faculty and students made proper use of virtual platforms and simultaneously met regulatory body requirements, thus ensuring that 'no student and faculty were left behind'. The responses varied from one HEI to another. The objective of this study was to present how a South African nursing education faculty managed teaching and learning following COVID-19-related interruptions. This included an HEI in KwaZulu-Natal, South Africa. Donabedian's tripartite model, comprising structure, process and outcome, provides the organising structure to present the faculty and university's approach to meet the desired outcome of saving the 2020 academic year. The Structures' and Processes' components of Donabedian's tripartite model influenced both intended and unintended outcomes. In 3 months, what might have been argued as impossible, a 4-year undergraduate nursing programme was transitioned from a traditional approach to fully virtual remote teaching and learning. Thus, the 2020 academic year was saved. Contribution: This article offers guidance to HEIs on how to continue teaching and learning in contexts where education is interrupted.